EP.WE.324Variation Between Observed and Perceived Volume of Antireflux Operations Completed by Upper-Gastrointestinal Surgeons at a University Teaching Hospital. (28th October 2021) - Ashmore, Christopher; Hunter, David; Boddy, Alex
Abstract: Aims: Increased institutional volume and surgeon experience with antireflux surgery has been shown to improve patient outcomes. We have sought to illustrate the discrepancy between the perceived (self-reported) and observed annual volume of anti-reflux operations completed by each surgeon. Method: A retrospective questionnaire was delivered to all upper-gastrointestinal (UGI) surgeons performing antireflux surgeries (ARS) at a University Teaching Hospital. Surgeons were asked to estimate the quantity of NHS antireflux cases completed annually. Objective, anonymised data was retrieved from the Surgical Workload Outcomes Audit Database (SWORD) from 2017 to 2020 for comparison. Results: 127 ARS were completed by 6 UGI consultants between January 2018 and December 2020. The median number of ARS completed per surgeon was 5 (2-10) in 2018, 9 (4-11) in 2019 and 10 (1-11) in 2020. Conversely, the median number of self-reported annual procedures per surgeon was 20 (12-35). On average, participants overestimated the number of NHS ARS completed by 14.5 (4-27) cases or a factor of 2.08. No surgeon correctly or underestimated the number of ARS performed. Conclusion: We conclude that self-reported operation volume should not be relied upon for the purposes of assessment or audit. Estimations of annual ARS procedures could be up to triple that suggested by objective data. Our data supports the importance of local or national data sets like SWORD to give an accurate reflection of practice and to allow individuals to compare their performance against their peers.